ІЗ ДОСВІДУ ПІДГОТОВКИ СТУДЕНТІВ ДО ПЕДАГОГІЧНОЇ ПРАКТИКИ У ЛІТНІХ ОЗДОРОВЧИХ ТАБОРАХ (Педагогіка вищої та середньої школи, 2010)
The structure of the training of the students third year of Krivoy Rog State Pedagogical University for pedagogical practice in summer camps is considered in flu article.